2019
DOI: 10.1155/2019/2496905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Thermo-Alkaline and Electro-Fenton Disintegration Effect on Waste Activated Sludge Anaerobic Digestion

Abstract: Disintegration of municipal waste activated sludge (WAS) using thermo-alkaline (TA) and electro-Fenton (EF) methods was investigated and compared in terms of the efficiency of sludge solubilisation and enhancement of anaerobic biodegradability. Performance of organic matter solubilisation (soluble COD, proteins, polysaccharides) of sludge pretreated with EF was proved to be better than that with TA pretreatment, which resulted in the enhancement of anaerobic biodegradability. Comparison of results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…A vast range of H 2 O 2 concentrations has been studied and significantly diverse results have been reported in the literature. Studies conducted by Feki et al 2019 [39] found an optimal H 2 O 2 concentration of 1.8 g/L for municipal sludge. To assess the impact of H 2 O 2 concentration, the other operating parameters were held constant (current density = 40 mA/cm 2 and time = 60 min) and the H 2 O 2 dosage was varied from 25 to 1000 mg/g-TS.…”
Section: Resultsmentioning
confidence: 96%
“…A vast range of H 2 O 2 concentrations has been studied and significantly diverse results have been reported in the literature. Studies conducted by Feki et al 2019 [39] found an optimal H 2 O 2 concentration of 1.8 g/L for municipal sludge. To assess the impact of H 2 O 2 concentration, the other operating parameters were held constant (current density = 40 mA/cm 2 and time = 60 min) and the H 2 O 2 dosage was varied from 25 to 1000 mg/g-TS.…”
Section: Resultsmentioning
confidence: 96%
“…As the electrolysis time increases from 1 to 4 h operation, the amount of nitrate, phosphorous, ammonia, and chemical oxygen demand increased from 3.83 to 4.89 mg L −1 , 102 to 160 mg L −1 , 72 to 88 mg L −1 and 2521 to 4745 mg L −1 , respectively which indicates solubilization of biosolids, and the production of chemicals such as ammonia. The increase in the soluble chemical oxygen demand is originated from the damage of the sludge structure and membrane cell wall and releasing the extracellular and intracellular organic matters into liquid phase [33]. The amount of ammonia released during electrolysis was higher than biosolid digestion, which specified that the applied voltage could accelerate the rate of protein hydrolysis [20].…”
Section: Effectiveness Of One Step Alkaline Electrolysis Vs Alkaline Treatmentmentioning
confidence: 99%